THEORIZING CAREER SUCCESS PERCEPTION AS A MEDIATOR BETWEEN MANAGERIAL LEARNING AND THE LEARNING ORGANIZATION - Maniam, Vikineswaran A (PEOPLE: International Journal of Social Sciences, 2017)
This analytical research paper was prepared by using literature review on the relationships among three variables composed of managerial learning, career success perception and the learning organization. Managerial learning is the exogenous variable whereas the learning organization is the endogenous variable. Career success perception is the third variable. Supported by literature review on the linkages among the three variables on the premises of cause and effect, the role of career success perception as a mediator was justified using Baron & Kenny’s (1986) criteria on properties of variables to distinctively differentiate between mediating and moderating variables. Henceforth, a model was suggested for future research using career success perception as the mediator between managerial learning and the learning organization.